2006
DOI: 10.1007/s00330-006-0373-4
|View full text |Cite
|
Sign up to set email alerts
|

Proton MRI appearance of cystic fibrosis: Comparison to CT

Abstract: Cystic fibrosis (CF) is the most frequent inherited disorder leading to premature death in the Caucasian population. As life expectancy is limited by pulmonary complications, repeated imaging [chest X-ray, multislice high-resolution computed tomography (MS-HRCT)] is required in the follow-up. Magnetic resonance imaging (MRI) of the lung parenchyma is a promising new diagnostic tool. Its value for imaging lung changes caused by CF compared with CT is demonstrated. MRI performs well when compared with CT, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 26 publications
(27 reference statements)
6
95
0
2
Order By: Relevance
“…The observations described here derive from two observational studies that found that CT scanning is more likely than CXR to accurately identify DLD in children (17,35), numerous case series that reported a strong correlation between histologic findings and the thin-section CT scan appearance in children with surfactant protein C mutation (42), neuroendocrine cell hyperplasia of infancy (NEHI) ( Figure 5) (20) and other DLDs (17,19,35), and two studies that demonstrated that CT scanning is superior to MRI in resolution and in identifying ground glass opacity, normal peripheral bronchi, and air trapping in patients with cystic fibrosis (43,44). Although cystic fibrosis is not a chILD disorder, resolution is an important determinant of image quality, and the findings of air trapping and ground glass opacity are key observations in chILD.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…The observations described here derive from two observational studies that found that CT scanning is more likely than CXR to accurately identify DLD in children (17,35), numerous case series that reported a strong correlation between histologic findings and the thin-section CT scan appearance in children with surfactant protein C mutation (42), neuroendocrine cell hyperplasia of infancy (NEHI) ( Figure 5) (20) and other DLDs (17,19,35), and two studies that demonstrated that CT scanning is superior to MRI in resolution and in identifying ground glass opacity, normal peripheral bronchi, and air trapping in patients with cystic fibrosis (43,44). Although cystic fibrosis is not a chILD disorder, resolution is an important determinant of image quality, and the findings of air trapping and ground glass opacity are key observations in chILD.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Computed tomography scores have been described to can be even more sensitive than pulmonary functional parameters in the detection of early CF lung disease and in determining the progression of lung manifestation. 10,29,37,38 Oikonomou et al 10 reported that simplification of the CT scoring systems provided even better findings than the original more extent scores. The more simplified structure of the Eichinger scoring system might be one main reason that the Eichinger score showed in general higher clinical correlations and stronger agreement between CT and MRI demonstrated in the Bland-Altman plot (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of the specific CT and MR imaging parameters, the following descriptions were used according to published definitions: -Bronchiectasis: 12,22,28,29 was defined as bronchial dilatation with respect to the accompanying pulmonary artery, lack of tapering of bronchi, and identification of bronchi within 1 cm of the pleural surface; in the modified Helbich score, the severity of bronchiectasis was estimated by comparing the bronchial luminal diameter with the size of the adjacent artery; -Peribronchial wall thickening 12,22 was separately assessed in the modified Helbich score in comparison with the adjacent artery; bronchiectasis and bronchial wall thickening were recorded as one single parameter in the Eichinger score; -Mucus plugging 12,21,22,28 was defined as fluid content within dilated bronchi greater than 3 mm without signal enhancement after contrast medium administration; peripheral mucus plugging can demonstrate a grapelike or "tree-in-bud" appearance. If mucus plugging was observed in the periphery, this segment or lobe was also scored for the parameter bronchiectasis; -Sacculation/abscess 12,22,29 was regarded as a circular structure with a diameter greater than 1.5 cm, which was air-filled or showed an air-fluid level and had a thick wall; -Collapse/consolidation 12,22,28,29 was defined as a homogeneous increase in pulmonary parenchymal density (CT) or signal intensity (MRI) with a size greater than 2 cm, which obscured the margins of vessels and airway walls; it can be caused by alveolar filling with inflammatory fluid and/or by atelectasis; -Bulla 12,28 was regarded as a sharply demarcated airspace with a diameter greater than 1 cm and a thin wall (<1 mm thickness) in the modified Helbich score (Table 2).…”
Section: Analysis Of Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on patient size and ability to breath-hold, it is useful to prepare three separate protocols (• ▶ Fig. 1 Table 2) [11,28,29]. Each should start with balanced steady-state free precession (bSSFP) sequences.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%